Media Pembelajaran dalam Pendidikan Pancasila dan Kewarganegaraan (PPKn) - Kusumawati, Intan; Mardianti, Desi; Paiman (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
Pancasila and Citizenship Education (PPKn) plays a strategic role in shaping the character, national insight, and democratic attitudes of students as the nation's future generation. Amidst technological advances and the challenges of the digital era, learning media are required to be more adaptive and innovative in order to bridge the delivery of PPKn values effectively and meaningfully. This study aims to examine various types of learning media used in PPKn learning, examine their effectiveness based on previous studies, and identify challenges faced in their implementation at various levels of education. This study uses a literature review approach by tracing references from scientific journals, academic books, and relevant documents published in the last ten years. The results of the study indicate that the use of learning media, both conventional and digital-based, has been proven to improve students' conceptual understanding, active participation, and reflective attitudes towards PPKn material. Interactive digital media such as quiz applications, learning videos, and web-based educational platforms are considered more effective in reaching the learning styles of the digital generation. However, its implementation still faces various obstacles, such as limited technological infrastructure, low teacher digital literacy, and a lack of media development that is contextually relevant to Civics (PPKn) material. In conclusion, this article recommends the need to develop learning media relevant to student needs and ongoing training for teachers to support improving the quality of Civics (PPKn) learning.